Design Alat Deteksi Gangguan Kerusakan Pada Kondisi Ic Cmos Logic Berbasis Komputer Memakai Software Delphi 5.0 - Gozali, R.B. Moch. (Lembaga Penerbitan Universitas Esa Unggul, 2006)
Science Growth and technological these days claim all party to work better again, especially at electronics area that is hit problem IC. Our Ignorance hit condition IC and type to can be stringed up inÃ‚Â network become big problem. Is for that needed by appliance to can know condition IC and type. Tester IC CMOS Appliance of through interface PPI 8255 which used computer by software is delphi 7 representing appliance which can be used to solve this problem. This appliance work givenly is input logic ofÃ‚Â IC examinee, later, then the Ã‚Â output logic data of quation by the tables of later truth taken by conclusion. By means of ... this, can know the way of connecting among between IC CMOS by IC is TTL of through medium CMOS network to TTL medium TTL network and to CMOS.Key word : Computer, IC CMOS, Interface PPI 8255, Driver Circuit